Penentuan Jenis Kelamin Menggunakan Metode Pengukuran Tulang Calcaneus di Berbagai Negara : Systematic Review - Dwi Putri Anggraini; Umi Salsabillah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The research aims to systematically review scientific journals that discuss sex determination using the calcaneus bone measurement method with the Systematic Literature Review method prepared based on the Preferred Reporting System for Systematic Reviews and Meta-Analyses (PRISMA) guidelines which have been registered in PROSPERO (CRD42020136170) . There are three scientific databases used as primary data search sources (PubMed, Science Direct and Google Scholar). Scientific articles that meet the criteria will be analyzed based on instruments that are often used in determining gender using measurements of the calcaneus bone. The search results produced 286 studies and only 17 scientific articles met the criteria. The population is different countries mentioned in 13 journals, where the other 3 journals mention the same location or country using the same tools or instruments, so that explanations will be represented per country, such as Greece and Ecuador. Meanwhile, Portugal has 1 other journal from the same country but has a different instrument so it will be included separately. Measuring tools or instruments that are often used to measure the calcaneus bone in determining gender are digital caliper, morphometric, GLM, BMD, X-ray, CT, Volume Analyze Synapse Vincent, Sahara, Specialized mini-osteometric and MRI. In conclusion, Digital Caliper and Morphometric are the tools or instruments most widely used in various countries in determining gender based on measurements of the calcaneus bone based on three categories of analysis, namely length measurements (MAXL, LAL, DAFL), width measurements (MAXB, MINB, DAFB), and height measurements (MAXH, BH, CFH).